PENGARUH BIAYA BAURAN PROMOSI TERHADAP OMZET PENJUALAN USAHA AGRIBISNIS DI DENPASAR - Niri Antari, Putu Evi Henda; Susrusa, Ketut Budi; Suamba, Ketut - (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2019)
ABSTRACT Marketing requires more than just developing a good product, set an attractive price, offering an affordable prices, but also need to promote the product itself. The success of a marketing program also determined by promotion mix. This research aimed to analyzed the influence of  promotion mix cost simultaneously, partially and the most dominantly variable toward the sales turnover of agribusiness company in Denpasar. The research method was used descriptive statistics. Through descriptive statistical analysis will be described and described characteristic table of respondents, while the influence of promotion mix cost to sales turnover using multiple linear regression analysed using the help of SPSS program version 22.0. Based  on  multiple  linear  analysis,  the  results     of  research  showed promotion mix variables give simultaneous positive and significant effect toward the   sales turnover p ? 0.05 with determination coefficient 0.575 or 57.5 %. Partially, all of five variables promotional mix showed that the cost of advertising, cost of personal selling, cost of sales promotion and cost of direct marketing give significant affect, while the variable cost of public relations showed insignificant results. The most dominant variable affecting the sales turnover is the cost of sales promotion with standardized beta coefficient point  to 0.463. Suggestions that can be given by the author to agribusiness entrepreneurs in Denpasar in order to implement promotional mix cost policies that are appropriate in the future to be in accordance with the capabilities and budget owned by the company. The combination of the five components of the promotional mix costs is still carried out, but must pay attention and consider allocating funds efficiently into the promotional mix costs so that the company does not experience losses.